Perspectives on endovascular training in traditional 5+2 vascular surgery fellowship training programs. (April 2016) - Carruthers, Thomas N; Shahmohammadi, Kaveh; Farber, Alik; Rybin, Denis; Doros, Gheorghe; McPhee, James T; Kalish, Jeffrey E; Eslami, Mohammad H
This study aimed to compare expectations and experiences of fellows to those of faculty in vascular surgery fellowship programs with regard to endovascular training. Anonymous surveys were sent to fellows (n = 235) and program directors (n = 147), with 79 fellows and 65 faculty members responding. Fellows noted higher expectations of their endovascular skills prior to starting fellowship than the faculty group reported expecting. Faculty assessed fellows' pre-training endovascular skills at a significantly lower level than the fellows' self-assessment. Fellows were significantly less satisfied with the structured aspects of endovascular training than the faculty believed them to be. Only 3% of fellows vs. 32% of faculty felt that the presence of an endovascular simulator affected how residents ranked fellowship programs during the match. In conclusion, incoming fellows in vascular surgery fellowship programs have high expectations of themselves, but may overestimate their actual pre-training endovascular skills. Fellows desire more structured endovascular training, which is not recognized by faculty. Endovascular simulators are valued, but may not be a significant draw in the match process.